1967
DOI: 10.1139/b67-042
|View full text |Cite
|
Sign up to set email alerts
|

Chytrids and Algae: I. Host–substrate Range, and Morphological Variation of Species of Rhizophydium

Abstract: Studies of pathogenicity and of morphological variation were made with pure cultures of IChizopkydiu?iz spkaerocarpum isolated from Spirogyra and of R. karlingii isolated from Ulothrix. R. splcaerocarpz~m was parasitic, virtually confined t o species of Spirogyra amongst which there was a wide range of susceptibility. R. karlingii grew only on non-living algae and on pine pollen. The rhizoidal system of R. splzaerocarpum was quite variable in the extent of its branching.Variations in sporangium size and of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…This method is useful not only to obtain fungal zoospores for experiments, but also to prevent the possible development of a resistant host strain (only zoospore suspensions are transferred to new host cultures, instead of using an infected host culture for inoculation of new host cultures, where the risk of transferring resistant hosts is increased). Culturing chytrids without host algae is also possible in artificial media (Barr & Hickman, 1967b) or on agar plates (Barr, 1987). Both methods with or without host algae, however, need special attention that bacteria should not outgrow the chytrids.…”
Section: Culturing Chytridsmentioning
confidence: 99%
“…This method is useful not only to obtain fungal zoospores for experiments, but also to prevent the possible development of a resistant host strain (only zoospore suspensions are transferred to new host cultures, instead of using an infected host culture for inoculation of new host cultures, where the risk of transferring resistant hosts is increased). Culturing chytrids without host algae is also possible in artificial media (Barr & Hickman, 1967b) or on agar plates (Barr, 1987). Both methods with or without host algae, however, need special attention that bacteria should not outgrow the chytrids.…”
Section: Culturing Chytridsmentioning
confidence: 99%
“…are both favoured by temperatures >15°C at optimum pH of about 7.3 (Sen 1988). Laboratory cultures and the maintenance of host -parasite systems growing under controlled conditions (Bruning & Ringelberg 1987, Bruning 1991 have suggested that the optimum temperature for fungal growth is highly variable and can be speciesspecific, generally ranging from 3°C (Van Donk & Ringelberg 1983) to 30°C (Barr & Hickman 1967). In freshwater environments, chytrids, especially those that infect diatoms, have a high affinity for low water temperatures (Ibelings et al 2003).…”
Section: Factors That Influence the Development Of Fungal Epidemicsmentioning
confidence: 99%
“…Amoebophrya species are mainly known as marine endoparasites in red-tide dinoflagellate blooms (Coats et al, 1996), and were intensively studied in oceans where they display a worldwide distribution (Park et al, 2004). In freshwater ecosystems, saprotrophs and parasites also include zoosporic fungi and some of them are host-specific to various phytoplankton species (Barr & Hickman, 1967;Gutman et al, 2009;Rasconi et al, 2009). …”
Section: Hidden Putative Ecological Potentials From Hfmentioning
confidence: 99%
“…More recent studies have indicated that the natural phytoplankton hosts indeed include both diverse populations of eukaryotic phytoplankton (Rasconi et al, 2009), and colonial and filamentous cyanobacteria in productive waters as well (Rasconi et al, 2009). Parasitic zoosporic fungi are often host specific, highly infective and extremely virulent in phytoplankton (Canter & Lund, 1951;Barr & Hickman, 1967;Holfeld, 1998;Gutman et al, 2009). They are considered relevant for the evolution of their hosts but also for the population dynamics and successions of phytoplankton communities (Van Donk & Ringelberg, 1983;De Bruin, 2006), with a prevalence of infection than can exceed 20% within a given population (Rasconi et al, 2009).…”
Section: Hidden Putative Ecological Potentials From Hfmentioning
confidence: 99%